Reference Range of Cerebrospinal Fluid Opening Pressure in Children: Historical Overview and Current Data - Avery, Robert A. (Neuropediatrics, 2014)
The lumbar puncture and cerebrospinal fluid (CSF) opening pressure (OP) in children remains an essential diagnostic test for children with suspected elevated intracranial pressure. Recent prospective data have revised the normative CSF OP values and described how clinical variables such as age, depth of sedation, and obesity may influence the measurements. In addition, the new normative data are now reflected in revised diagnostic criteria for idiopathic intracranial hypertension/pseudotumor cerebri syndrome. This review highlights the recently published data and provides guidance on how it may impact clinical management.
Keywords: opening pressure; cerebrospinal fluid; intracranial hypertension; pseudotumor cerebri; papilledema; lumbar puncture